Interplay between Structural and Thermoelectric Properties in Epitaxial Sb2+xTe3 Alloys. (20th November 2018) - Cecchi, Stefano; Dragoni, Daniele; Kriegner, Dominik; Tisbi, Elisa; Zallo, Eugenio; Arciprete, Fabrizio; Holý, Václav; Bernasconi, Marco; Calarco, Raffaella
Abstract: In recent years strain engineering is proposed in chalcogenide superlattices (SLs) to shape in particular the switching functionality for phase change memory applications. This is possible in Sb2 Te3 /GeTe heterostructures leveraging on the peculiar behavior of Sb2 Te3, in between covalently bonded and weakly bonded materials. In the present study, the structural and thermoelectric (TE) properties of epitaxial Sb2+ x Te3 films are shown, as they represent an intriguing option to expand the horizon of strain engineering in such SLs. Samples with composition between Sb2 Te3 and Sb4 Te3 are prepared by molecular beam epitaxy. A combination of X‐ray diffraction and Raman spectroscopy, together with dedicated simulations, allows unveiling the structural characteristics of the alloys. A consistent evaluation of the structural disorder characterizing the material is drawn as well as the presence of both Sb2 and Sb4 slabs is detected. A strong link exists among structural and TE properties, the latter having implications also in phase change SLs. A further improvement of the TE performances may be achieved by accurately engineering the intrinsic disorder. The possibility to tune the strain in designed Sb2+ x Te3 /GeTe SLs by controlling at the nanoscale the 2D character of the Sb2+ x Te3 alloys is envisioned. Abstract : The precise tuning of the properties of epitaxial Sb2+ x Te3 in between those of 2D and 3D materials is established. It paves the way to expand the horizon of strain engineering in phase change memory superlattice structures. The interplay between structural and thermoelectric properties in these alloys is presented.